Peripheral nerve injury repair by electrical stimulation combined with graphene-based scaffolds - Zhao, Yuanyuan; Liu, Yang; Kang, Shiqi; Sun, Daokuan; Liu, Yufeng; Wang, Xin; Lu, Laijin (Frontiers in Bioengineering and Biotechnology, 2024)
Peripheral nerve injury (PNI) is a common clinical problem, which due to poor recovery often leads to limb dysfunction and sensory abnormalities in patients. Tissue-engineered nerve guidance conduits (NGCs) that are designed and fabricated from different materials are the potential alternative to nerve autografts. However, translation of these NGCs from lab to commercial scale has not been well achieved. Complete functional recovery with the aid of NGCs in PNI becomes a topic of general interest in tissue engineering and regeneration medicine. Electrical stimulation (ES) has been widely used for many years as an effective physical method to promote nerve repair in both pre-clinical and clinical settings. Similarly, ES of conductive and electroactive materials with a broad range of electrical properties has been shown to facilitate the guidance of axons and enhance the regeneration. Graphene and its derivatives possess unique physicochemical and biological properties, which make them a promising outlook for the development of synthetic scaffolds or NGCs for PNI repair, especially in combination with ES. Considering the discussion regarding ES for the treatment of PNI must continue into further detail, herein, we focus on the role of ES in PNI repair and the molecular mechanism behind the ES therapy for PNI, providing a summary of recent advances in context of graphene-based scaffolds (GBSs) in combination with ES. Future perspectives and some challenges faced in developing GBSs are also highlighted with the aim of promoting their clinical applications.